Towards Higher Complexity in the RNA World: Hairpin Ribozyme Supported RNA Recombination. Issue 4 (25th February 2021) - Hieronymus, Robert; Müller, Sabine
Abstract: In the RNA world, the exchange of sequence patches between two RNAs is an intriguing evolutionary concept, allowing generation of new RNA molecules with novel functionality. Based on the hairpin ribozyme (HPR) with its unique cleavage‐ligation properties, we here demonstrate RNA supported RNA recombination as a possible scenario for the emergence of larger RNA molecules with more complex functionality. A HPR variant designed for the purpose of recombination is capable of cleaving two different RNA molecules, one being a hammerhead ribozyme (HHR) and the other an aptamer (A), and to subsequently recombine and ligate the resulting fragments to a hammerhead ribozyme that is allosterically controlled (HHA) by a cognate ligand. Two such recombination processes involving aptamers for either theophylline or flavine mononucleotide (FMN) are demonstrated with yields of functional recombination product of up to 34 %. Abstract : RNA world : Recombination may have played a central role in the RNA world for the generation of RNA molecules with novel functions. A small catalytic RNA derived from the hairpin ribozyme acts as RNA recombinase supporting the extension of ribozyme catalyzed RNA cleavage to an allosterically controlled process. Aptazymes responding to theophylline or FMN as cognate ligands are produced by ribozyme supported recombination.